2009
DOI: 10.2752/175303708x390464
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Human Interaction, Animal-Assisted Therapy, and AIBO-Assisted Therapy on Long-Term Care Residents with Dementia

Abstract: The number of elderly people in the United States is projected to more than double to 80 million by the year 2050, which will likely result in an increased incidence of dementia. Although AAT programs have been instituted as therapeutic activities for residents of long-term care facilities, there is little research documenting their effectiveness, especially in patients with dementia, who have difficulty maintaining contact with the external world. In addition, some long-term care facilities may be reluctant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 16 publications
(22 reference statements)
1
85
0
3
Order By: Relevance
“…One study compared the effects of visitation by a person, a person accompanied by a live dog, and a person accompanied by a robotic pet. [19] All three types of visits stimulated positive social interactions in female nursing home residents with dementia. Conversation, touches and looks, and smiling and laughing were stimulated by all three visits with no significant differences among the three.…”
Section: Discussionmentioning
confidence: 99%
“…One study compared the effects of visitation by a person, a person accompanied by a live dog, and a person accompanied by a robotic pet. [19] All three types of visits stimulated positive social interactions in female nursing home residents with dementia. Conversation, touches and looks, and smiling and laughing were stimulated by all three visits with no significant differences among the three.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, dementia is the leading cause of disability of Canadians over the age of 65 with significant economic costs expected to rise to $153 billion dollars by 2038 [2]. Similar issues exist in other countries such as Japan and the United States, where the increasing aging demographic and declining traditional caregiver demographic have driven the search for innovative dementia care strategies [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies reveal positive attitudes towards robotic dogs [10]. In one small short term study in an American residential home, Aido was found to stimulate more social interaction than a real dog [11].…”
Section: Use Of Social Robots For Pwdmentioning
confidence: 99%